Why can't I walk upside-down? - Penn, Julie; Abdi (Glasgow : Collins, 2021)
What do you know about spiders? Inspire a love of reading with stories that are written from a child's perspective and will encourage children to discover the world around them. With audio and activities, Peapod Readers are the perfect start to a child's journey into learning English. Includes: Before and after reading activities. Picture dictionary. Exam practice for Cambridge Pre A1 Starters. Reading guide online
Primary
Keywords: Readers (Primary); Readers (Publications); Spiders -- Juvenile literature